ABNORMAL CSR AND FINANCIAL PERFORMANCE: DOES SIZE MATTER? - Jessica Frisianti Setiady; Ilyona Risty (COMPETITIVE, 2026)
This study examines the effect of abnormal Corporate Social Responsibility (CSR) on the financial performance of manufacturing firms listed on the Indonesia Stock Exchange (IDX) during 2019–2024, and tests the moderating role of firm size. This study employs a quantitative research approach using purposive sampling to obtain 168 firm-year observations from manufacturing companies listed on the Indonesia Stock Exchange (IDX) during 2019–2024. The study uses secondary data derived from companies’ annual and sustainability reports available on the IDX website. Data were analyzed using multiple linear regression with a panel data model to examine the effect of abnormal CSR on financial performance and to test the moderating role of firm size. Abnormal CSR has a negative effect on firm financial performance, and the first hypothesis is accepted, means that when a company's CSR activities deviate significantly from what is considered normal or expected in the industry, it tends to harm its financial results. This could occur because excessive or misaligned CSR spending may be perceived as inefficient resource allocation, potentially reducing profitability. Abnormal CSR reduces profitability, but larger firms can moderate its negative impact through better asset efficiency. Firms should align CSR spending with strategic goals to sustain legitimacy and financial performance